Many Hands without Design: The Evolution of a Medieval Prophetic Text - Holdenried, Anke (The Mediaeval Journal, 2014)
Abstract This article reconstructs the pre-manuscript history of the Sibylla Tiburtina, a late antique prophetic text, which was very widespread after c. 1000. It argues against the prevailing belief that a single intelligence structured the Latin text to a single meaning in the eleventh century. By identifying early medieval interpolations this article offers a new account of the work’s textual development in the centuries before 1000. This suggests the text known as the Ottonian Sibyl had a far less distinct moment of creation than is usually assumed and was actually the product of interpolators independently adding to its late antique core over a long period and without a common purpose.